Particle charging in beam-plasma systems - Bizyukov, А.А.; Romashchenko, E.V.; Sereda, K.N.; Abolmasov, S.N. (Вопросы атомной науки и техники, 2013)
The particle charging in an electron beam-plasma discharge is studied by means of the classical orbit motion limited approximation and on the basis of a discrete charging model. The particle charge fluctuations due to the stochastic nature of charging process are considered. The Fokker-Planck description of the particle charging has been presented. An analytical expression for the charge distribution function has been derived taking into account the processes of the collection of plasma electrons and ions by the dust grain and secondary electron emission from it. В рамках классического приближения ограниченного орбитального движения и на основе дискретной модели изучается зарядка частиц в пучково-плазменных разрядах. Рассматриваются флуктуации заряда частиц, связанных со случайностью процесса зарядки. Представлено описание Фоккера-Планка зарядки частиц. Выведено аналитическое выражение для функции распределения заряда с учетом процессов поглощения электронов и ионов плазмы пылевой частицей и с учетом вторичной электронной эмиссии. У рамках класичного наближення обмеженого орбітального руху та на підставі дискретної моделі вивчається зарядження частинок у пучково-плазмових системах. Розглянуто флуктуації зарядження частинок, пов’язаних з випадковістю процесу зарядження. Представлено опис Фоккера-Планка зарядження частинок. Отримано аналітичний вираз для функції розподілу заряду, з урахуванням процесів поглинання електронів та іонів плазми пиловою частинкою та з урахуванням вторинної електронної емісії.